Dogs zoonoses and public health [ - Macpherson, C. N. L. [ (Calum N. L.)]; Meslin, F.-X. [ (Francois-X.)]; Wandeler, Alexander I. (CABI, 2012)
Zoonotic diseases constitute a public health problem throughout the world. Addressing a little studied area of veterinary and medical science, this book covers the viruses, bacteria and protozoan and helminth parasites that are transmitted between man ad dogs, discussing population management, control disease agents and human-dog relationships. Fully updated throughout, this new edition also includes two new chapters on benefits of the human-dog relationship and non-infectious disease issues with dogs. It is a valuable resource for researchers and students of veterinary and human medicine, microbiology, parasitology and public health.